Influence of vacancies on the mechanical and thermodynamic properties of TM2B3(TM=Ru and Os) borides from first-principles calculations. Issue 17 (1st December 2019) - Pan, Y.; Jing, C.
Abstract: The layered structure plays an important role in Vickers hardness of superhard materials. However, the Vickers hardness of transition metal borides with layered structure is influenced by the defect. By means of first-principles approach, we studies the influence of vacancy on the Vickers hardness, elastic modulus and thermodynamic properties of TM2 B3 (TM = Ru and Os). Two vacancy types: B-vacancy (B-va ) and TM-vacancy (TM-va ) are considered. The result shows that B-va and TM-va are thermodynamically stable in Ru2 B3 and Os2 B3 . The TM-va vacancy is more thermodynamically stable than that of the B-va vacancy. It is found that B-va and TM-va vacancies weaken the deformation resistance of TM2 B3 . However, B-va vacancy enhances the Vickers hardness of Ru2 B3 and Os-va vacancy improves the Vickers hardness of Os2 B3 . In addition, we find that TM-va and B-va vacancies improve the thermodynamic properties of TM2 B3 .